2018
DOI: 10.11114/jets.v6i12.3452
|View full text |Cite
|
Sign up to set email alerts
|

The Social Media Addiction Among Turkish University Students

Abstract: The objective of this study is to examine the place and importance of social media in the lives of university students according to several demographic variables. 323 Turkish students in total, 186 of whom were males and 137 of whom were females, studying in different departments at Selçuk University, participated in the study. A personal information form was used to obtain the socio-demographical information of the students, while “Social Media Addiction Scale” (SMAS), developed by Tutgun Ünal (2015), was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
(16 reference statements)
0
20
0
4
Order By: Relevance
“…This instance could be evidence that the players joining from the bench might be one of the most critical variables affecting the results of the matches. According to Altin and Kivrak (2014), all of the players must be ready all the time for any changes in the field. Players must re-position themselves quickly and adequately for changing parameters such as in-field settings, ball positions, player strategies, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This instance could be evidence that the players joining from the bench might be one of the most critical variables affecting the results of the matches. According to Altin and Kivrak (2014), all of the players must be ready all the time for any changes in the field. Players must re-position themselves quickly and adequately for changing parameters such as in-field settings, ball positions, player strategies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The professional leagues exist in Brazil, Italy, Spain, Portugal, France and many other countries. Futsal, outshining with dribbling, ball control techniques and shoting styles is a very entertaining sports game for spectators (Barbero-Alvarez et al, 2009;Altin & Kivrak, 2014;Ocak & Bugdayci, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our country as of year 2005, two studies revealed that 27.1% and 51.7% of university students and as of 2014 56.5% of university students were playing video games. 11,12 According to a research study conducted in 2009 one out of every three people above 15-years-old were video gamers, 34% of the gamers were 18-24 years of age, and 47.3% of the 18-24 years of age group were playing video games. 13 Besides in 2009, it was observed that 86.9% of video gamers preferred computers, 44.7% game consoles, and 11.8% mobile phones as platforms for gaming.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on undergraduates and teenagers evaluate social media addiction on the basis of a demographic variables (Çam and İşbulan, 2012;Aydın and Çelik, 2017;Baz,2018;Çiftçi,2018;Tutgun-Ünal,2015;Yılmazsoy and Kahraman,2017;Sanal-Özcan and Özer, 2017). Şeyda and Diken, 2018;Deniz and Gürültü, 2018;Karaman and Kurtoğlu, 2009;Baş and Diktaş, 2020), social media usage behaviors (Kırık et al,2015;Altin and Kivrak, 2018;Aktan,2018;Tutgun-Ünal, 2019;Afacan and Özbek, 2019;Tutgun-Ünal, 2020;Yesilyurt and Turhan, 2020) and psychological factors and problems (Özgür,2013;Balcı and Baloğlu, 2018;Uzun, Yıldırım and Uzun, 2016;Sahin, 2017;Kırcaburun, 2016;Bilgin, 2018;Balcı, Bekiroğlu and Karaman, 2019;Karadağ and Akçınar, 2019;Eşer and Alkaya, 2019;Köse and Doğan, 2019;Baltacı,2019;Hamutoglu, Topal and Gezgin, 2020).…”
Section: Social Media Addictionmentioning
confidence: 99%